The pattern for Prisoners in Coaching Skills Class II B Sinjai - Ernawati Ernawati; Kiki Rasmala Sani; Karmilayana Karmilayana (Jurnal Ad'ministrare, 2020)
This study aims to determine the Pattern of Guidance for Prisoners in Class II B Detention Centers  in Sinjai Regency. The research method used is a qualitative approach with data collection through observation, in-depth interviews, and documentation. The informants consisted of the head of the detention center, the head of the prison service sub-section, the detention security unit, staff, and six prisoners. The data analysis technique used the Miles and Huberman method. Based on the results of the research, the Correctional Assistance residents who are equipped with skills training, not only spend time in the cell but can develop themselves according to their interests and talents by utilizing the facilities and infrastructure provided by the detention center even though there are still obstacles in its implementation, such as funds, raw materials, management and motivation of the inmates.